2018
DOI: 10.1177/1933719118799195
|View full text |Cite
|
Sign up to set email alerts
|

Further Evidence for Hypercoagulability in Women With Ovarian Endometriomas

Abstract: Our previous studies have shown that platelets play a crucial role in the development of endometriosis, and women with endometriosis appear to be in a state of hypercoagulability. However, a recent study could only replicate part of our previous finding, casting doubts on this notion. We further investigated this question through a cross-sectional study by measuring additional coagulation factors in women with and without endometriosis. To this end, we conducted a cross-sectional study of 100 women with laparo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 39 publications
(66 reference statements)
3
26
0
Order By: Relevance
“…Three studies have evaluated differences in INR between patients with and without endometriosis finding no difference [12,14,29]. Four studies have addressed aPTT [12,14,29,30], and two of them have reported shortened aPTT in cases when compared to controls [12,14]. In particular, in our previous study, considering the various manifestations of endometriosis separately, we found that women with ovarian disease had shortened aPTT values in comparison to controls and women with SPE and DIE.…”
Section: Results Of the Systematic Reviewmentioning
confidence: 73%
See 4 more Smart Citations
“…Three studies have evaluated differences in INR between patients with and without endometriosis finding no difference [12,14,29]. Four studies have addressed aPTT [12,14,29,30], and two of them have reported shortened aPTT in cases when compared to controls [12,14]. In particular, in our previous study, considering the various manifestations of endometriosis separately, we found that women with ovarian disease had shortened aPTT values in comparison to controls and women with SPE and DIE.…”
Section: Results Of the Systematic Reviewmentioning
confidence: 73%
“…Opposite results were obtained by Kim and coworkers, since PLC was not significantly different in severe endometriosis [27]. Three studies have evaluated PT [12,29,30], and only Ding and coworkers showed a significantly shorter time in the OMA group compared to a benign cyst group and a control group [30]. Conversely, for TT, three studies [12,29,30] out of four showed significantly shorter values in patients affected by OMAs compared to control groups [12,14,29,30].…”
Section: Results Of the Systematic Reviewmentioning
confidence: 84%
See 3 more Smart Citations